RANCANG BANGUN SISTEM INFORMASI PENJUALAN SPAREPART GENERAL DIESEL DI CV MULTI MANDIRI BERBASIS WEB - Pernando, Pernando; Saragih, Saut Pintubipar (Computer Science and Industrial Engineering, 2020)
The development of technology is currently growing, one of which is the development of online, which is very fast, many companies have started to offer their spare parts online to be able to leave the maximum profit, so that competition between companies is increasing both for spare parts and for services. company: this is why CV Multi Mandiri needs to create a web marketing information system so that consumers can easily access information about spare parts, because they can directly order and pay for spare parts through the website. The method used is the SDLC waterfall model, which consists of needs analysis, design, software code, testing, marketing, and maintenance. The result of this research is a website-based marketing information system that allows consumers to easily order products to order spare parts and saves employees time and money.